Sur une chronique arabo-berbère des Ibāḍites médiévaux - Ould-Braham, Ouahmi (Études et Documents Berbères, 1988)
The aim of this article is to take into consideration the historical and social climate in which the chronicle studied by Lewicki 1934a was composed, and to edit Arab-Berber fragments copied by Motylinski from an Ibāḍī MS when he was in Mīzāb, to serve as a comparison (o.c., 5). On pp. 8-13 a list of Ibāḍī historical works is given (the relation with old Berber is not clear). Pp.13-14 on Ibāḍī works in Berber that might have existed. Pp. 14-16 on the chronicle already studied by Lewicki 1934a. Pp. 16-28: passages from this chronicle, assembled by Motylinski to serve as a working dossier for his article “Le nom berbère de Dieu chez les Abadhites”, with translations. Little, or no, new information is added to Lewicki 1934a and 1936 (qq.v.).
Keywords: Linguistique

Le berbère en Tunisie - Boukous, Ahmed (Études et Documents Berbères, 1988)
Keywords: Linguistique